Dinamika Politik Lokal di Awal Orde Baru: Kemenangan Partai NU dalam Pemilu 1971 di Kabupaten Surabaya - Shodiqur Rohman, Fathu; Widiastuti, Eko Hari; Kusairi, Latif; Mahmud (Universitas Negeri Semarang, 2025)
This paper analyzes the victory of the Nahdlatul Ulama (NU) Party in the 1971 General Election in Surabaya Regency as part of the local political dynamics during the early New Order period. Using a political history approach and a qualitative-descriptive method, the article examines the social, cultural, and political strategies that contributed to NU's success. Data were collected through literature review, archival documentation, and interviews with historical witnesses and community leaders. The findings indicate that the network of Islamic boarding schools (pesantren) and traditional clerics (kiai) played a crucial role in consolidating grassroots support, while the post-G30S social climate and public distrust toward secular parties further strengthened NU’s position. These findings demonstrate that, despite the pressure of a New Order regime that supported Golkar, traditional Islamic cultural forces were still able to carve out political victories at the local level. This study contributes to a deeper understanding of how local cultural power can persist and even triumph within a centralized political system.